Grisotti flap for central quadrant breast tumours: quick, cosmetic and easy to learn – a case series - Sharma Shivaji; Pao Karan (Visualized Cancer Medicine)
Background: Breast cancer surgery has moved away from mutilating mastectomies to organ preservation approach keeping in mind the cosmetic outcome. Centrally located tumours are particularly notorious as they often require resection of the nipple-areola complex (NAC) thus creating a gross cosmetic defect. However, cosmesis is possible even after such surgeries. Methods: Seven consecutive patients with centrally located breast tumours were subjected to breast conservation surgery – either upfront or after neoadjuvant chemotherapy – followed by reconstruction with Grisotti flap. All patients were followed up for a minimum period of 3 months after surgery. None of them had any flap related complications and reported satisfactory cosmetic outcome with no loss of body image. Interpretation: Lumpectomy with resection of the NAC with Grisotti flap reconstruction is a relatively fast procedure with a short learning curve. In our case series of 7 women, all underwent successful breast reconstruction with minimum morbidity and excellent cosmetic outcome.